Processo de remediação enzimática de agentes dos nervos: cálculos de ancoramento molecular e mecanismo de reação - Castro, Alexandre Alves de (2016)
During World War II, organophosphorus agents (OP) with neurotoxic action were developed and used as the basis for the development of structures used today in the agricultural industry, such as pesticides. Among the neurotoxic agents there are the chemical weapons Tabun (GA), Sarin (GB), Soman (GD) and VX. The toxicity of these compounds is due to inhibition of Acetylcholinesterase (AChE), the enzyme responsible for the hydrolysis of the Acetylcholine (ACh) neurotransmitter. Two of the enzymes characterized with potential to degrade OP are Phosphotriesterase (PTE) and the Human Serum Paraoxonase 1 (HuPON1). These enzymes have generated considerable interest for rapid and complete detoxification applications. Due to the importance of bioremediation methods for the intoxication caused by OP, this work aims to study the interaction of these enzymes with different neurotoxic agents, taking into account the "Rp" and "Sp" isomers for each compound. Molecular Docking, Homology modeling, Molecular Dynamics (MD) and QM/MM techniques were used. In the case of PTE, its metallic center was also modified, and according to the theoretical calculations, it brought about benefits in relation to the increase of its catalytic activity. For HuPON1, in addition to the wild-type enzyme, the calculations were also developed for two mutant enzymes. The computational investigations provided important and relevant data for a better understanding of the bacterial PTE and human PON1 performance in OP nerve agents.